Fair TDMA scheduling in wireless multihop networks - Vergados, Dimitrios J.; Sgora, Aggeliki; Vergados, Dimitrios D.; Vouyioukas, Demosthenes; Anagnostopoulos, Ioannis (Telecommunication systems, 2012)
In wireless multihop networks, communication between two end-nodes is carried out by hopping over multiple wireless links. However, the fact that each node has to transmit not only its own traffic, but also traffic on behalf of other nodes, leads to unfairness among the communication rates of the nodes. Traditional Carrier Sense Multiple Access/Collision Avoidance (CSMA/CA) based media access control does not work satisfactory in a multihop scenario, since an intended target of a communication may be subject to mutual interference imposed by concurrent transmissions from nodes, which cannot directly sense each other, thus causing unfair throughput allocation. Although Time Division Multiple Access (TDMA) seems to be a more promising solution, careful transmission scheduling is needed in order to achieve error-free communication and fairness. Several algorithms may be found in the literature for scheduling TDMA transmissions in wireless multihop networks. Their main goal is to determine the optimal scheduling, in order to increase the capacity and reduce the delay for a given network topology, though they do not consider the traffic requirements of the active flows of the multihop network or fairness issues. In this paper, we propose a joint TDMA scheduling/load balancing algorithm, called Load-Balanced-Fair Flow Vector Scheduling Algorithm (LB-FFVSA). This algorithm schedules the transmissions in a fair manner, in terms of throughput per connection, taking into account the communication requirements of the active flows of the network. Simulation results show that the proposed algorithm achieves improved performance compared to other solutions, not only in terms of fairness, but also in terms of throughput. Moreover, it was proved that when a load balancing technique is used, the performance of the scheduling algorithm is further improved.